Innovative Attitude Assessment in Islamic Education: Techniques, Instruments, and Technology Integration from Primary to Higher Education - Damayanti, Novita; Nida, Sofwatun; Rahmawati, Nur Widya; Hidayat, Yusron; Mandar, Yasri; Hidayah, Ahwil Lutan (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study examines innovations in attitude assessment within Islamic educational institutions, including madrasahs, pesantrens, and formal schools at the primary, secondary, and tertiary levels. The main focus is to develop affective assessment techniques and instruments that are contextually appropriate, methodologically sound, and aligned with core Islamic values such as honesty, patience, empathy, and responsibility. Using a qualitative approach through literature review and historical analysis, the study reviews primary policy documents and relevant scholarly literature. Thematic analysis reveals weaknesses in conventional assessment methods, including subjectivity, limited integration of Islamic ethical values, and a lack of adaptive systems. At the primary level, assessments rely heavily on observation and anecdotal records, which often lead to subjective results. At the secondary level, self- and peer-assessments are commonly used but are vulnerable to bias. In higher education, more contextual approaches such as case-based assessments and portfolios demonstrate better alignment with character education goals. The study highlights the potential of digital innovations, including artificial intelligence and online platforms, to enhance the accuracy and scalability of attitude assessments. These tools offer promising solutions to longstanding challenges by enabling deeper integration of Islamic values in affective evaluation. The study recommends developing standardized yet adaptable digital instruments, along with improved teacher training and curriculum development, to support effective Islamic value-based assessments.